Future zoonis forecasting of Betacoronavirus group using phylogenetics and haplotype network analysis - Rahmat Grahadi; Rizka Vamelia Sulistya Ningrum; Najma Zahira; Nia Kurniawan; Fatchiyah Fatchiyah (The East Java Biological Society, 2020)
Genetic diversity and species relationship contribute to the inter-species transmission of coronavirus-derived diseases. This research aimed to investigate the probability of newly emergence Betacoronavirus zoonosis according to genetic relationship and haplotype network. A total of 24 Betacoronavirus sequences from different continents were used to construct the phylogenetic tree and the haplotype network. A phylogenetic tree was constructed using the Maximum Likelihood method with RaxML in CIPRES Science Gateway portal and GTRGAMMA+I analysis with 1000 bootstrap. Haplotype Network was done using Network 10.0.0.0 version with median-joining analysis. The result of the phylogenetic and haplotype network formed 4 groups of Betacoronavirus. Group A consisted of Human Coronavirus (HCoV) type OC43 and HKU1, Bovine Coronavirus, and Rodent Coronavirus. Group B consisted of SARS-CoV and SARS-CoV-2. Group C consisted of MERS-CoV (2012 pandemic) and MERS-CoV from camels. Reliable with phylogenetic results, haplotype network also grouped Betacoronaviruses into three groups in accordance with their subgenera. Bovine and Rodent coronavirus are constant to group with previously human coronavirus, i.e. HCoV-OC43 and HCoV-HKU1, respectively. According to the high genetic similarity that the Bovine and Rodent coronavirus may infect to human and provide a new emergence. This study is basic for further research related to inter-species transmission from animal to human.